Students' perceptions of history fieldwork ICSS in relation to vision 2020, Malaysia - Salleh, Mohamad Johdi; Madin, Abu Bakar (Association of Indonesian Scholars of History Education (ASPENSI), 2009)
The Malaysian government and the agencies had allocated and spent millions of ringgits to preserve and decorate the national heritage such as the museums, archives, gallery, artefacts, sites, and other historical remains. These were not wasteful when the record showed that local and international people were continuously visiting these sites located across the country. These are also became major tourist attraction which indirectly inculcated knowledge and enhanced appreciation upon the practices of multi-ethnic and multi-cultural Malaysian. Thus, this paper discusses a study on the students’ perceptions of fieldwork approaches to history of the Integrated Curriculum for Secondary Schools (ICSS) Malaysia in relation to the challenges of Vision 2020. The study was conducted in various types of schools in Perak and Terengganu which involved about eight hundred students. The instruments used were questionnaire and interview. The data was analysed by using SPSS and presented in percentage and numerical. The result of the study shows a high relation concerning the students’ perceptions of fieldwork approaches of history and the challenges of Vision 2020. It is hoped that more students would benefit from this core subject of the lower and upper secondary levels, ICSS Malaysia, towards the development of the twenty-first millennium first class human capital of Malaysian and 1-Malaysia nation.